Reformulating the Limits of Fixed-Term Employment Agreements in Repeated Contract Extension Practices to Prevent Abuse by Employers - Tricho Dike Fierrera; Afdhal (Indonesian Journal Publisher, 2026)
This study aims to analyze and reformulate the limits of Fixed-Term Employment Agreements (PKWT) in the Indonesian labor law system, as an effort to balance labor market flexibility and worker protection. This study uses a normative juridical method with a statutory and conceptual approach, examining the provisions in Law Number 13 of 2003 concerning Manpower as amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, as well as Government Regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing of Working Hours and Rest Hours, and Termination of Employment. The research results indicate normative weaknesses in the form of unclear contract extension limits, multiple interpretations of norms, and weak supervision and law enforcement, which open up room for abuse of PKWT (Fixed Term Employment Agreements) in practice, such as the use of fixed-term contracts for permanent employment and repeated contract extensions without clear limits. Therefore, reformulation of PKWT regulations is needed by establishing a maximum extension limit, a cumulative duration limit, an automatic conversion mechanism to an Indefinite-Term Employment Agreement (PKWTT), and strengthened sanctions and oversight. This reformulation is expected to create legal certainty, prevent abuse, and realize equitable industrial relations.